2010
DOI: 10.1111/j.1445-6664.2010.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of internationally traded wheat by herbicide‐resistant Lolium rigidum

Abstract: As herbicide-resistant weeds have spread in the agricultural fields of grain-exporting countries, their seeds could be introduced into other countries as contaminants in imported grain.The spread of resistance genes through seed and pollen can cause significant economic loss. In order to assess the extent of the problem, we investigated the contamination by herbicide-resistant annual ryegrass (Lolium rigidum) of wheat imported from Western Australia into Japan. Annual ryegrass seeds were recovered from wheat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…A less frequent form of resistance spread, but still worth underlining, is via seed import from regions with high infestation of resistant grass weeds. For instance, analysis of a 20 kg batch of Australian wheat exported to Japan in 2006 identified as many as 4673 L. rigidum seeds, 35% of which were resistant to diclofop‐methyl …”
Section: Occurrence Evolution and Spread Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…A less frequent form of resistance spread, but still worth underlining, is via seed import from regions with high infestation of resistant grass weeds. For instance, analysis of a 20 kg batch of Australian wheat exported to Japan in 2006 identified as many as 4673 L. rigidum seeds, 35% of which were resistant to diclofop‐methyl …”
Section: Occurrence Evolution and Spread Of Resistancementioning
confidence: 99%
“…For instance, analysis of a 20 kg batch of Australian wheat exported to Japan in 2006 identified as many as 4673 L. rigidum seeds, 35% of which were resistant to diclofop-methyl. 73 Importantly, once resistance to ACCase herbicides has been established, it is difficult to overcome even with the use of other herbicide modes of action and alternative methods of weed control combined. A black-grass study conducted over a 6-year period has shown that while different cropping systems and other herbicide modes of action can result in an overall decline in the weed seed bank, the frequency of ACCase-resistant individuals within the field did not decrease over this timeframe.…”
Section: Occurrence Evolution and Spread Of Resistancementioning
confidence: 99%
“…Seeds of Lolium species were picked out from each wheat sample following the method described in Shimono et al . (). These seeds were provided by the National Institute for Agro‐Environmental Sciences to Y. Shimono at Kyoto University and were stored in an airtight container with silica gel at room temperature (20–28°C) until the experiments.…”
Section: Methodsmentioning
confidence: 97%
“…Weed seeds spread through the sharing of equipment among farmers, the use of non‐composted manure and the use of contaminated commercial seed stocks or feed (Thill & Mallory‐Smith, ; Barroso et al ., ; Shimono & Konuma, ). Recent studies have shown that many herbicide‐resistant weed seeds are contaminants in commercial grain (Michael et al ., ; Shimono et al ., ). For example, herbicide‐resistant Lolium rigidum Gaudin seeds have been detected as contaminants in wheat from Western Australia imported into Japan (Shimono et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation